Readiness of Future Music Teachers on the Basis of the Praxeology Approach: Essence, Structure, Development Criteria - Provorova , Ievgeniia (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The article analyzes the essence of the concept “methodical readiness of future music teacher on the basis of praxeology approach”. The paper shows the result of methodical preparation in higher pedagogical educational institution that reflects the system of needs, motivations, imagination, values, the ability to broadcast or create innovations for improvisation, to forecast the results of own activities; high level of informative knowledge in the field of music art and techniques, skills of use own voice, facial expressions, gestures, techniques and methods for generating and analyzing ideas, successfully apply praxeology educational technologies that maintain the success of musical and pedagogical (singing) activity. The researcher outlined motivationally-valuable, emotional and volitional, cognitive-reflective, creative-projective, behavioral, personally-resulted, organizationally-communicative components, criteria and indicators of analyzed phenomenon